Preventive health behavior and Health Locus of control among Young People in the Time of Corona - Rezigue, Manel; Rouag, Abla; Benharkat, Imene (Journal of Human Sciences, 2023)
This study aimed to investigate the relationship between preventive health behavior and health locus control among young people in the time of COVID, through conducting a semi-oriented interview to be analyzed.  In this study, we found out that the impact of the Corona virus was extremely negative on both physical and mental health, for both infected and non-infected people. The results of the study showed that many unhealthy behaviors appeared among adults because of the ignorance of the nature of this virus, its degree of danger, and the way how to prevent it, We have also concluded that the source of health control contributes to the adoption of preventive behaviors, so that the source of internal control promotes respect for preventive measures, unlike external regulators who attribute the infection to the surrounding environment, without taking into account the necessary preventive measures, which makes it more difficult to control the spread of infection.